Lymph/angiogenesis contributes to sex differences in lung cancer through oestrogen receptor alpha signalling. Issue 2 (February 2019) - Dubois, Charline; Rocks, Natacha; Blacher, Silvia; Primac, Irina; Gallez, Anne; García-Caballero, Melissa; Gérard, Céline; Brouchet, Laurent; Noël, Agnès; Lenfant, Françoise; Cataldo, Didier; Pequeux, Christel
Abstract : Oestrogen signalling pathways are emerging targets for lung cancer therapy. Unravelling the contribution of oestrogens in lung cancer development is a pre-requisite to support the development of sex-based treatments and identify patients who could potentially benefit from anti-oestrogen treatments. In this study, we highlight the contribution of lymphatic and blood endothelia in the sex-dependent modulation of lung cancer. The orthotopic graft of syngeneic lung cancer cells into immunocompetent mice showed that lung tumours grow faster in female mice than in males. Moreover, oestradiol (E2) promoted tumour development, increased lymph/angiogenesis and VEGFA and bFGF levels in lung tumours of females through an oestrogen receptor (ER) alpha-dependent pathway. Furthermore, while treatment with ERb antagonist was inefficient, ERa antagonist (MPP) and tamoxifen decreased lung tumour volumes, altered blood and lymphatic vasculature and reduced VEGFA and bFGF levels in females, but not in males. Finally, the quantification of lymphatic and blood vasculature of lung adenocarcinoma biopsies from patients aged between 35 and 55 years revealed more extensive lymphangiogenesis and angiogenesis in tumour samples issued from women than from men. In conclusion, our findings highlight an E2/ERa-dependent modulation of lymphatic and blood vascular components of lung tumour microenvironment. Our study has potential clinical implication in a personalised medicine perspective by pointing to the importance of oestrogen status or supplementation on lung cancer development that should be considered to adapt therapeutic strategies.